Prevalence of postpartum family planning utilization and associated factors among postpartum mothers in Arba Minch town, South Ethiopia - Biresaw Wassihun; Kidist Wosen; Asmare Getie; Kalkidan Belay; Rehal Tesfaye; Tewodros Tadesse; Yosef Alemayehu; Manaye Yihune; Addis Aklilu; Kassahun Gebayehu; Shegaw Zeleke (BMC, 2021)
Abstract Background Contraception allows women to realize their human right to decide if and when to have children and helps people to attain their desired family size. Yet 214 million women of a reproductive age in developing countries who want to avoid pregnancy are not using a modern contraceptive method. Women who have recently given birth are among the group with the highest unmet need for contraception. Therefore, this study was aimed to assess the prevalence of postpartum family planning use and associated factors among postpartum women in Southern Ethiopia. Methods Institution based cross-sectional study design was conducted. A structured and pretested interviewer-administered questionnaire was used to collect the data from study participants. Study participants were selected using a systematic random sampling technique by allocating proportionally to each health facility. The data was entered using EPI data version 3.1statistical software and exported to Statistical Package for Social Sciences version 22.0 for further analysis. Both bivariate and multivariate logistic regression analyses were performed to identify associated factors. P values < 0.05 with 95% confidence level was used to declare statistica significance. Result Overall, 44% of postpartum women utilize postpartum family planning. Having an antenatal care visit [adjusted odds ratio (AOR) =1.89(95%CI, 2.42-7.90), having planned pregnancy [adjusted odds ratio (AOR) = 1.17(95%CI, 1.60-2.28)], being married (adjusted odds ratio (AOR) =2.86(1.94-8.73), and having a college and above level educational status (AOR) =1.66(1.28-3.55) were significantly associated with utilization of postpartum family planning. Conclusion This study showed that the prevalence of postpartum family planning was 44%. Marital status, educational status of mothers, the status of pregnancy, and having an antenatal care follow-up during pregnancy were some factors associated with postpartum family planning utilization. Therefore, strengthening family planning counselling during antenatal and postnatal care visits, improving utilization of postnatal care services and improving women's educational status are crucial steps to enhance contraceptive use among postpartum women.